Comparing the mechanical strength of wooden chairs constructed using two patterns and mortise and tenon and dowel joints - Ali Bayatkashkoli (Regional Information Center for Science and Technology (RICeST), 2014)
Member joints and furniture designs are very important in the production of these elements and the strength of the structure is affected by both the joints and designs. The performance of the chairs made from poplar wood against the front to back load test and also, mechanical strength of mortise and tenon and dowel joints were evaluated and compared. Two types common wooden chairs having side stretcher or without side stretcher, and also the chairs structured by common joints and poly vinyl acetate (PVA) adhesive are evaluated and their maximum strength were measured. The results showed that treatments and intercept treatments were statistically significant with the 95% confidence. Duncan analysis for comparison of the averages showed that maximum load of different treatments can be classified into four category; A; Pattern of side stretcher with mortise and tenon joint (984.5 N), B; Pattern of side stretcher with dowel joint (892.4 N), C; Pattern without side stretcher with mortise and tenon joint (303.3 N), D;  Pattern without side stretcher with dowel joint (260.2 N). Since, all treatments showed statistically significant differences, it can be conclude that the maximum strength of the chairs is significantly influenced by the pattern of side stretcher and the other factor is the mortise and tenon joint.